Structural mechanism of heat-induced opening of a temperature-sensitive TRP channel - Nadezhdin, Kirill D; Neuberger, Arthur; Trofimov, Yuri A; Krylov, Nikolay A; Sinica, Viktor; Kupko, Nikita; Vlachova, Viktorie; Zakharian, Eleonora; Efremov, Roman G; Sobolevsky, Alexander I (Nature structural & molecular biology, 2021)
Numerous physiological functions rely on distinguishing temperature through temperature-sensitive transient receptor potential channels (thermo-TRPs). Although the function of thermo-TRPs has been studied extensively, structural determination of their heat- and cold-activated states has remained a challenge. Here, we present cryo-EM structures of the nanodisc-reconstituted wild-type mouse TRPV3 in three distinct conformations: closed, heat-activated sensitized and open states. The heat-induced transformations of TRPV3 are accompanied by changes in the secondary structure of the S2-S3 linker and the N and C termini and represent a conformational wave that links these parts of the protein to a lipid occupying the vanilloid binding site. State-dependent differences in the behavior of bound lipids suggest their active role in thermo-TRP temperature-dependent gating. Our structural data, supported by physiological recordings and molecular dynamics simulations, provide an insight for understanding the molecular mechanism of temperature sensing.
Keywords: Protein Binding; TRPV Cation Channels; Ion Channel Gating; Cell Line; vnímání teploty; HEK293 buňky; Thermodynamics; Cryoelectron Microscopy; gating iontového kanálu; HEK293 Cells; termodynamika; vazba proteinů; lipidy; Animals; lidé; elektronová kryomikroskopie; konformace proteinů; Humans; zvířata; vysoká teplota; myši; buněčné linie; Lipids; Protein Conformation; Mice; kationtové kanály TRPV; Thermosensing; nízká teplota; Hot Temperature; Cold Temperature